Application of Optimal Homotopy Asymptotic Method to Doubly Wave Solutions of the Coupled Drinfel'd-Sokolov-Wilson Equations. (8th December 2013) - Ullah, H.; Islam, S.; Idrees, M.; Nawaz, R.
Abstract : The approximate solution of the doubly periodic wave solutions of the coupled Drinfel'd-Sokolov-Wilson equations has been considered by using the optimal homotopy asymptotic method (OHAM). We obtained the numerical solution of the problem and compared that with the OHAM solution. The obtained solutions show that OHAM is effective, simpler, easier, and explicit and gives a suitable way to control the convergence of the approximate solution.